2020
DOI: 10.1021/acsphotonics.0c01245
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on Ultraviolet Disinfection Systems against COVID-19 Outbreak: Applicability, Validation, and Safety Considerations

Abstract: The global health-threatening crisis from the COVID-19 pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), highlights the scientific and engineering potentials of applying ultraviolet (UV) disinfection technologies for biocontaminated air and surfaces as the major media for disease transmission. Nowadays, various environmental public settings worldwide, from hospitals and health care facilities to shopping malls and airports, are considering implementation of UV disinfection d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
300
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(318 citation statements)
references
References 88 publications
(172 reference statements)
6
300
1
11
Order By: Relevance
“…While the biological effects of DUV light have been widely proven across different types of viruses 14,[16][17][18][19][28][29][30][31][32] , the precise mechanism by which the DUV light inactivates viruses remains to be elucidated 19 . Several studies reported that virus inactivation by DUV irradiation is primarily caused by the photochemical reactions of nucleic acids 19,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…While the biological effects of DUV light have been widely proven across different types of viruses 14,[16][17][18][19][28][29][30][31][32] , the precise mechanism by which the DUV light inactivates viruses remains to be elucidated 19 . Several studies reported that virus inactivation by DUV irradiation is primarily caused by the photochemical reactions of nucleic acids 19,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…While the biological effects of DUV light have been widely proven across different types of viruses [14,[16][17][18][27][28][29][30][31], the precise mechanism by which the DUV light inactivates viruses remains to be elucidated [18]. Several studies reported that virus inactivation by DUV irradiation is primarily caused by the photochemical reactions of nucleic acids [18,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial properties of ultraviolet radiation from mercury vapor lamps are well known and have been applied for over a hundred years [ 1 ]. They have also proven to be effective against coronaviruses [ 2 ], [ 3 ].…”
Section: Introductionmentioning
confidence: 99%